2005
DOI: 10.1002/neu.20209
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation in the Rana catesbeiana auditory medulla over metamorphic development

Abstract: During metamorphic development, bullfrogs (Rana catesbeiana) undergo substantial morphological, anatomical, and physiological changes as the animals prepare for the transition from a fully-aquatic to a semi-terrestrial existence. Using BrdU incorporation and immunohistochemistry, we quantify changes in cell proliferation in two key auditory brainstem nuclei, the dorsolateral nucleus and the superior olivary nucleus, over the course of larval and early postmetamorphic development. From hatchling through early l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…The limitation of the immersion method is that beyond a certain animal size (S47), immersion is not an effective means for BrdU delivery to the otic vesicle. In our experiments, the efficacy of BrdU administration by im'mersion was confirmed in all specimens in this study through the presence of BrdU-positive cells in the ventricular zone of the brain (Chapman et al, 2006).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The limitation of the immersion method is that beyond a certain animal size (S47), immersion is not an effective means for BrdU delivery to the otic vesicle. In our experiments, the efficacy of BrdU administration by im'mersion was confirmed in all specimens in this study through the presence of BrdU-positive cells in the ventricular zone of the brain (Chapman et al, 2006).…”
Section: Discussionsupporting
confidence: 69%
“…Amphibians such as Xenopus offer an alternative model for unraveling mechanisms that promote regeneration in an organism that is well characterized genetically and developmentally (Nieuwkoop and Faber, 1967;Amaya, 2005). Furthermore, the increasing interest in the use of amphibians such as Xenopus to investigate cell proliferation during development of the olfactory bulb (Fritz et al, 1996), the spinal cord (Schlosser et al, 2002) and the auditory medulla (Chapman et al, 2006), will provide a foundation for comparative studies of the regenerative potential of amphibian neural and sensory tissue as compared with that of other vertebrates. Here we have demonstrated the spatial and temporal patterns that characterize cell proliferation in the developing X. laevis inner ear during the period leading to the initial compartmentalization of auditory and vestibular structures at S47, as well as the contribution of cells that had undergone terminal mitosis during earlier stages to the formation of the emerging S47 sensory epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Chapman et al [2006] observed stage-specific changes in cell proliferation in both the DMN and the SON, with peaks of cell birth in the early (DMN, SON) or late (DMN) larval periods, a decline during the deaf period, and a subsequent peak in metamorphic climax. Similarly, Templin and Simmons [2005] observed a decline in the number of differentiated neurons in the SON beginning during the deaf period and extending into the early stages of metamorphic climax.…”
Section: Possible Mechanisms Of Anatomical Reorganizationmentioning
confidence: 99%
“…Boundaries in the adult brain are based on Matesz [1979], Wilczynski [1981], Montgomery [1988], Will and Fritzsch [1988], Feng and Lin [1991], McCormick [1999] and Matesz et al [2002]. The DMN has been variously called the nucleus cochlearis [Larsell, 1934;Matesz, 1979], the acoustic nucleus [Jacoby and Rubinson, 1983] and the dorsal lateral nucleus Chapman et al, 2006]. What we are identifying as the anterior lateral line nucleus Opdam et al [1976].…”
Section: Anatomical Boundaries and Terminologymentioning
confidence: 99%
See 1 more Smart Citation